Phenotypic and functional alterations of myeloid-derived suppressor cells during the disease course of multiple sclerosis - Iacobaeus, Ellen; Douagi, Iyadh; Jitschin, Regina; Marcusson-Stahl, Maritha; Andren, Anton Toernqvist; Gavin, Caroline; Lefsihane, Katia; Davies, Lindsay C.; Mougiakakos, Dimitrios; Kadri, Nadir; Le Blanc, Katarina (Immunology and Cell Biology, 2018)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system involving dysregulated encephalitogenic T cells. Myeloid-derived suppressor cells (MDSCs) have been recognized for their important function in regulating T-cell responses. Recent studies have indicated a role for MDSCs in autoimmune diseases, but their significance in MS is not clear. Here, we assessed the frequencies of CD14+ HLA-DRlow monocytic MDSCs (Mo-MDSCs) and CD33+ CD15+ CD11b+ HLA-DRlow granulocytic MDSCs (Gr-MDSCs) and investigated phenotypic and functional differences of Mo-MDSCs at different clinical stages of MS and in healthy subjects (HC). Increased frequencies of Mo-MDSCs (P < 0.05) and Gr-MDSCs (P < 0.05) were observed in relapsing-remitting MS patients during relapse (RRMS-relapse) compared to stable RRMS (RRMS-rem). Secondary progressive MS (SPMS) patients displayed a decreased frequency of Mo-MDSCs and Gr-MDSCs compared to HC (P < 0.05). Mo-MDSCs within RRMS patients expressed significantly higher cell surface protein levels of CD86 and CD163 compared to SPMS patients. Mo-MDSCs within SPMS exhibited decreased mRNA expression of interleukin-10 and heme oxygenase 1 compared to RRMS and HC. Analysis of T-cell regulatory function of Mo-MDSCs demonstrated T-cell suppressive capacity in RRMS and HCs, while Mo-MDSCs of SPMS promoted autologous T-cell proliferation, which aligned with a differential cytokine profile compared to RRMS and HCs. This study is the first to show phenotypic and functional shifts of MDSCs between clinical stages of MS, suggesting a role for MDSCs as a therapeutic target to prevent MS disease progression.
EVALuna2:35092